2019
DOI: 10.31593/ijeat.518973
|View full text |Cite
|
Sign up to set email alerts
|

Particle mass and gaseous emissions from small scale modern wood stoves

Abstract: The objectives of the paper were to evaluate particle mass concentrations of PM1 (size <1 µm) and PM2.5 (size <2.5 µm), mass size distributions and CO emissions under standard laboratory conditions obtained from two commercially available modern residential wood stoves with capacity 10 kW and 20 kW. Four combustion batches with minor modification of primary air flows into the combustion chamber for each stove were conducted to evaluate the emission results. Particle mass concentrations and size distributions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The combustion of fuels leads to the formation of gaseous and particulate matter pollutants that have an impact on air quality and the environment. Several studies have shown that increased particle concentrations in the ambient air correlate with adverse health effects in the exposed population, including respiratory and cardiovascular illnesses as well as increased mortality human health [1][2][3][4][5][6][7]. Traditionally, particle emission measurements from the small scale biomass combustion technologies are performed in undiluted hot flue gases at temperatures of about 120-280 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combustion of fuels leads to the formation of gaseous and particulate matter pollutants that have an impact on air quality and the environment. Several studies have shown that increased particle concentrations in the ambient air correlate with adverse health effects in the exposed population, including respiratory and cardiovascular illnesses as well as increased mortality human health [1][2][3][4][5][6][7]. Traditionally, particle emission measurements from the small scale biomass combustion technologies are performed in undiluted hot flue gases at temperatures of about 120-280 °C.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of instruments can be used for the particle measurement and the selection and combination of instruments depends on the objectives. Measurements of particles are conducted in terms of mass concentrations, number concentrations and their size distributions [5,11]. Electrical Low Pressure Impactor Plus (ELPI+) is one of the widely used for measurements of particles in real time.…”
Section: Introductionmentioning
confidence: 99%